Digital Mediation and Community Narratives in Heritage Tourism: Reframing Authenticity in Melaka, Malaysia - Bin Azizan, Muhammad Arif Fitri; MD Syed, MD Azalanshah; Shamshudeen, Rosya Izyanie (Centre For Tourism Planning and Development, 2025)
This study examines how digital media and grassroots community participation mediate the experience of authenticity in Melaka, Malaysia, a UNESCO World Heritage city. Drawing on qualitative interviews with twenty participants, we apply the Cultural Authenticity-Spectrum Model (CASM) to interpret findings. CASM conceptualizes authenticity as a continuum rather than a binary, allowing analysis of experiences ranging from staged tourist pseudo-events to spontaneous local encounters. Tourists in Melaka reported mixed responses: many were influenced by curated social media imagery and enjoyed colorful spectacles, while others sought deeper connections through unscripted interactions with residents. Local stakeholders described balancing digital promotions and event staging with efforts to maintain cultural integrity, including community-led tours and consultative heritage branding. Key themes include the tension between spectacle and substance, the impact of social media versus on-site “analog” intimacy, and community empowerment versus marginalization. The study connects these insights with theories of staged and existential authenticity, showing how digital technology can both enhance and dilute perceived authenticity, and how community narratives can reclaim heritage meaning. Recommendations include co-creating tourism experiences with local communities, using digital storytelling to educate rather than simply entertain, and implementing policies that support authenticity alongside innovation. This research extends authenticity theory through the CASM framework and offers practical guidance for sustainable heritage tourism management in Southeast Asia.